Tone production in Mandarin-speaking children with cochlear implants: a preliminary study - Xu, Li; Li, Yongxin; Hao, Jianping; Chen, Xiuwu; Xue, Steve A.; Han, Demin (Acta oto-laryngologica, 2004)
Objective More than a quarter of the world's population speak tone languages, such as Mandarin Chinese. In those languages, the pitch or tone pattern of a monosyllabic word conveys lexical meaning. The purpose of this study was to investigate tone production in Mandarin-speaking children with cochlear implants (CIs). Material and Methods Speech samples were recorded from seven normal-hearing and four CI children aged 4-9 years. All subjects were native Mandarin speakers. The speech samples were used for acoustic analysis of the tone patterns, i.e. the fundamental frequency contours. In addition, a tone intelligibility test was carried out in which four normal-hearing native Mandarin-speaking adults listened to the speech materials and judged the intelligibility of the children's tone production. Results The tone production for the seven normal-hearing children was considered to be perfect in the intelligibility test. Acoustic analysis of the speech materials of the normal-hearing children produced the four typical tone patterns of Mandarin Chinese: (i) high and flat; (ii) rising; (iii) low and dipping; and (iv) falling. The tone patterns produced by the children with CIs tended to be flat, with some other patterns being irregular. The results of the tone intelligibility tests also showed degraded intelligibility of tone patterns. Conclusion A potential speech development deficit was documented in prelingually deafened children with CIs whose native language is a tone language. The imperfect tone production of the implant children, which can be attributed to the paucity of pitch information delivered via the current CI stimulation, may have significant implications for communication using tone languages. Further research is warranted to determine factors that may affect tone development in children with CIs.